The growth consequences of socialism - Andreas Bergh; Christian Bjørnskov; Luděk Kouba (Research Institute of Industrial Economics (IFN), 2024)
The discussion of the growth consequences of socialism has fulminated for a century, sparked off by the Calculation Debate in the 1920s and 30s, and has concerned the performance of the Soviet Union in the 1950s and the mixed development in the 1990s after communism collapsed in Central and Eastern Europe. We aim to inform these debates by providing an empirical assessment of how socialist economies performed across the second half of the 20th century. Using both neighbour comparisons as well as more formal empirical analysis of developing countries that turned socialist after independence, we derive a set of estimates of the degree to which the introduction of a planned socialist economy affects long-run growth and development. All analyses point towards an annual growth decline of approximately two percentage points during the first decade after implementing socialism.
Keywords: O11; O43; P20; 330; Economic growth; socialism